2016
DOI: 10.15575/jpi.v1i3.680
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Teacher Characters Basis of Tasawuf

Abstract: This paper is based on the reality of education system in Indonesia which is still far from expectations, especially in shaping the character of teachers and students. In various cases, it is still found sexual abuse committed by teachers and students as well as the number of users and drug addicts among students. The purpose of this research is to find the root causes of problems and workable solutions to build the characters of teachers and students in the education system in Indonesia. The method used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Prasetyo et al, (2019) suggest that teachers with good character can assist students in developing their own character. Muhammad & Dian (2016) reported that sufism can play a crucial role in instilling akhlak karimah values among teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…Prasetyo et al, (2019) suggest that teachers with good character can assist students in developing their own character. Muhammad & Dian (2016) reported that sufism can play a crucial role in instilling akhlak karimah values among teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…Malay manuscripts are the creative products of the Malay people, written by authors in the Archipelago (such as Syaikh Hamzah Fansuri, Syaikh Syamsuddin As-Samatrani, Syaikh Abdurrauf As-Singkeli, Syaikh Abdush Shamad bin Abdullah al-Jawi al-Falimbani, Syaikh Yusuf Al-Makassary, Syaikh Nawawi al-Bantani Al-Jawi, and Syaikh Muhammad Arsyad al-Banjari, as well as authors outside the Archipelago, such as Syaikh Nuruddin Ar-Raniry, Syaikh Muhammad bin Fadhlullah al-Burhanpuri al-Hindi, Syaikh Daud bin Abdullah al-Fattani, and Syaikh Zainal Abidin bin Muhammad al-Fattani [1]. They produced a number of manuscripts dealing with various religious topics, such as fiqh (Islamic jurisprudence), manthiq (logic), and tasawuf (mysticism) ( [2], [3], [4]).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sufi groups, immoral desires can be divided into two categories: physical and mental (spiritual). This mental category is more dangerous than physical form, because the unconscious makes people do worse things [28].…”
mentioning
confidence: 99%